2016
DOI: 10.2139/ssrn.2777484
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shift from Micro to Macro-Prudential Thinking: A Discursive Network Analysis

Abstract: While some economists argued for macro-prudential regulation pre-crisis, the macro-prudential approach and its emphasis on endogenously created systemic risk have only gained prominence post-crisis. Employing discourse and network analysis on samples of the most cited scholarly works on banking regulation as well as on systemic risk (60 sources each) from 1985 to 2014, we analyze the shift from micro to macro-prudential thinking in the shift to the post crisis period. Our analysis demonstrates that the predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The literature on economic ideas in international financial institutions used mostly qualitative methods (Mommani ; Broome and Seabrooke ; Clift ), combinations of text and network analysis (Ban ; Ban et al ; Thiemann et al ) and some statistical tests of the relationship between graduate training and economic ideas (Chwieroth ). Jeffrey Chwieroth, for example, showed that the IMF's advocacy of current account liberalization coincided with the New Classical turn in the US economics departments the IMF recruits from (Chwieroth , ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on economic ideas in international financial institutions used mostly qualitative methods (Mommani ; Broome and Seabrooke ; Clift ), combinations of text and network analysis (Ban ; Ban et al ; Thiemann et al ) and some statistical tests of the relationship between graduate training and economic ideas (Chwieroth ). Jeffrey Chwieroth, for example, showed that the IMF's advocacy of current account liberalization coincided with the New Classical turn in the US economics departments the IMF recruits from (Chwieroth , ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature gained more rigour when Leonard Seabrooke and Emelie Nilsson (2015) used sequence analysis to trace the flows of new staff from the private sector and into the IMF, yet without establishing their impact on the Fund's policy doctrine. Others still combined qualitative analysis and descriptive network analysis to map out political conditions under which international financial institutions embraced new economic thinking in academia in order to change some parts of their policy doctrine (Ban et al ; Thiemann et al ). Finally, although more advanced forms of quantitative text analysis entered the scene, they did not connect the ideas to specific scientific alliances between the thinking of issue professionals in the policy institutions and the other niches of the economics profession that supplied them with evidence, models or new ways of conceptualizing economic challenges (Güven ; Moschella and Pinto 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation